2022
DOI: 10.3389/fmed.2022.796424
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction Model of Immunosuppressive Medication Non-adherence for Renal Transplant Patients Based on Machine Learning Technology

Abstract: ObjectivesPredicting adherence to immunosuppressive medication (IM) is important to improve and design future prospective, personalized interventions in Chinese renal transplant patients (RTPs).MethodsA retrospective, multicenter, cross-sectional study was performed in 1,191 RTPs from October 2020 to February 2021 in China. The BAASIS was used as the standard to determine the adherence of the patients. Variables of the combined theory, including the general data, the HBM, the TPB, the BMQ, the PSSS and the GSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…The inclusion criteria were as follows: (1) age ≥18 years; (2) no graft failure after kidney transplant; (3) no exercise taboo (such as paralysis, osteoarthropathy, and cardiopulmonary disease); KTRs who were not Mandarin-speaking, had multiple transplantations, with cognition/mental disorders, and with postoperative time <3 months were excluded. A total of 1011 KTRs were enrolled in the derivation set and 180 in the validation set [ 12 ]. The flowchart of enrollment is illustrated in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were as follows: (1) age ≥18 years; (2) no graft failure after kidney transplant; (3) no exercise taboo (such as paralysis, osteoarthropathy, and cardiopulmonary disease); KTRs who were not Mandarin-speaking, had multiple transplantations, with cognition/mental disorders, and with postoperative time <3 months were excluded. A total of 1011 KTRs were enrolled in the derivation set and 180 in the validation set [ 12 ]. The flowchart of enrollment is illustrated in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al. [ 12 ] developed a prediction model based on machine learning technology and presented the predicted results by formulation, which was complex to apply to clinical practice. So far, few models were practical and well-suited to predict IM nonadherence in KTRs, and an innovative model that is theory-based, comprehensive, and easy to apply is needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed model is applicable only after transplant. More recently, Zhu et al, 56 using support vector machine technology, a machine learning algorithm used for classification problems, developed a predictive tool based on 10 variables and reported an AUC of 0.75. Again, the tool is applicable only on posttransplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sridharan et al [98] identified significant predictors useful in optimizing tacrolimus and cyclosporine dosing regimens using various ML algorithms. Zhu et al's [99] study on non-adherence found the SVM model to be the most effective, with a sensitivity of 0.59, a specificity of 0.73, and an average AUC of 0.75. Monitoring and managing disease recurrence in a transplanted organ is another vital aspect of post-transplant care.…”
Section: Personalized Post-transplant Managementmentioning
confidence: 99%